Pedagogical Content Knowledge, Religious Self-Concept, and Academic Achievement: Mediation of Intrinsic Religious Orientation - Syafii, hisyam; Azhari , Husain; Alaldaya, Rudyn (Yayasan Al Hidayah, 2026)
Academic success in religious studies is a complex phenomenon necessitating a thorough comprehension of pedagogical, psychological, and spiritual elements within educational settings. This study examines the intricate relationship between Pedagogical Content Knowledge (PCK), Religious Self-Concept, and their impact on academic accomplishment, mediated by Intrinsic Religious Orientation among students in Yogyakarta. A quantitative cross-sectional survey design was utilized including 150 students from senior high schools and Islamic high schools in Yogyakarta. Data were gathered utilizing validated tools that assess Pedagogical Content Knowledge (PCK), Religious Self-Concept, Intrinsic Religious Orientation, and Academic Achievement. Structural Equation Modeling (SEM) using AMOS 24.0 was performed to examine direct and indirect effects, whereas mediation analysis utilized bootstrapping techniques with 5,000 samples. The results indicate substantial direct impacts of Pedagogical Content Knowledge (PCK) on Academic Achievement (β = 0.342, p < 0.001) and of Religious Self-Concept on Academic Achievement (β = 0.186, p = 0.025). Intrinsic Religious Orientation acts as a notable partial mediator in both associations, exhibiting indirect effects of β = 0.116 (p = 0.006) for PCK and β = 0.177 (p = 0.001) for Religious Self-Concept. The model accounts for 68.4% of the variance in Academic Achievement, validating the theoretical synthesis of Shulman's PCK theory with Allport's religious orientation theory within educational frameworks.